Population birth outcomes in 2020 and experiences of expectant mothers during the COVID-19 pandemic: A 'born in Wales' mixed methods study using routine data. - Hope Jones; Mike Seaborne; Laura Cowley; David Odd; Shantini Paranjothy; Ashley Akbari; Sinead Brophy (PLoS ONE)
Background Pregnancy can be a stressful time and the COVID-19 pandemic has affected all aspects of life. This study aims to investigate the pandemic impact on pregnancy experience, rates of primary childhood immunisations and the differences in birth outcomes in during 2020 to those of previous years. Methods Self-reported pregnancy experience: 215 expectant mothers (aged 16+) in Wales completed an online survey about their experiences of pregnancy during the pandemic. The qualitative survey data was analysed using codebook thematic analysis. Population-level birth outcomes in Wales: Stillbirths, prematurity, birth weight and Caesarean section births before (2016-2019) and during (2020) the pandemic were compared using anonymised individual-level, population-scale routine data held in the Secure Anonymised Information Linkage (SAIL) Databank. Uptake of the first three scheduled primary childhood immunisations were compared between 2019 and 2020. Findings The pandemic had a negative impact on the mental health of 71% of survey respondents, who reported anxiety, stress and loneliness; this was associated with attending scans without their partner, giving birth alone, and minimal contact with midwives. There was no significant difference in annual outcomes including gestation and birth weight, stillbirths, and Caesarean sections for infants born in 2020 compared to 2016-2019. There was an increase in late term births (≥42 weeks gestation) during the first lockdown (OR: 1.28, p = 0.019) and a decrease in moderate to late preterm births (32-36 weeks gestation) during the second lockdown (OR: 0.74, p = 0.001). Fewer babies were born in 2020 (N = 29,031) compared to 2016-2019 (average N = 32,582). All babies received their immunisations in 2020, but there were minor delays in the timings of immunisations. Those due at 8-weeks were 8% less likely to be on time (within 28-days) and at 16-weeks, they were 19% less likely to be on time. Interpretation Whilst the pandemic had a negative impact on mothers' experiences of pregnancy. Population-level data suggests that this did not translate to adverse birth outcomes for babies born during the pandemic.